Knowledge of and Adherence to Anaemia Prevention Strategies among Pregnant Women Attending Antenatal Care Facilities in Juaboso District in Western-North Region, Ghana - Prince Kubi Appiah; Daniel Nkuah; Duut Abdulai Bonchel (Journal of Pregnancy)
Background. Anaemia in pregnancy is a major problem in both developed and developing countries. The commonest source of anaemia is nutritional deficiency of iron with evidence suggesting that up to 90% of maternal anaemia may be due to inadequate consumption of dietary iron; however, there are other causes which include worm infestation, HIV infection, and genetic disorders. There are some implemented approaches in Ghana including education and awareness creation, nutritional supplements, and control and prevention of parasitic infections among others to prevent and control anaemia in pregnancy. This study assessed pregnant women adherence to Ghana’s anaemia prevention strategies being implemented in the Juaboso District. Method. A descriptive cross-sectional data on knowledge of and adherence to anaemia prevention strategies among pregnant women was collected. Pearson’s chi-square and logistic regression models were used to assessed associations between predictor and outcome variables. A p value <0.05 was considered as statistically significant. Findings. About 13.5% of the pregnant women had high knowledge on anaemia, while 58.4% and 28.1% had moderate and low knowledge, respectively. Less than half (39.1%) of the women adhered to anaemia prevention strategies. There were significant associations between knowledge of anaemia and where pregnant woman resides in the district (AOR: 2.04, 95% CI: 2.16-9.83, p=0.003), woman’s educational (AOR: 10.43, 95% CI: 6.14-51.63, p=0.002), and occupational status (AOR: 15.14, 95% CI: 13.57-18.43, p<0.001). Again, there were significant associations between adherence to anaemia prevention strategies and the woman’s ethnicity (AOR: 0.61, 95% CI: 0.04-0.92, p=0.001) and her knowledge of anaemia (AOR: 3.88, 95% CI: 1.32-7.93, p=0.001). Conclusions. Pregnant women’s knowledge of anaemia and adherence to anaemia prevention strategies are not encouraging. However, anaemia in pregnancy and its consequences could be devastating to all stakeholders if actions are not taken to reduce the phenomenon. Therefore, we recommend that more education and sensitisation programs including good nutritional practices in the diet of pregnant women be promoted to increase awareness and adherence to anaemia prevention strategies among pregnant women in the Juaboso District.